Kali Linux cookbook effective penetration testing solutions - Schultz, Corey P.; Perciaccante, Bob (Packt Publishing Ltd., 2017)
Kali Linux is a Linux distribution designed for penetration testing and security auditing. It is the successor to BackTrack, the world's most popular penetration testing distribution. Kali Linux is the most widely used platform and toolkit for penetration testing. Security is currently the hottest field in technology with a projected need for millions of security professionals. This book ocuses on enhancing your knowledge in Kali Linux for security by expanding your skills with toolkits and frameworks that can increase your value as a security professional.